Finite Element Analysis of CM247LC Superalloy for Gas Turbine Blade Application - Chavan, Tejan; Khedkar, Nitin (Engineering, Technology & Applied Science Research, 2025)
The objective of this article is to conduct a comparative analysis of the various materials used in the production of gas turbine blades. The materials under investigation include CM247LC, Nimonic 80A, and Inconel 738. The selected blade materials are required to demonstrate exceptional resistance to high temperatures and corrosion. It is determined that the most appropriate material for the construction of a gas turbine blade is a nickel-based superalloy. For the purposes of Finite Element Analysis (FEA), the aforementioned materials are defined as nickel-based superalloys. A comprehensive analysis of these materials was conducted using the ANSYS 2024 R2 student edition and a combination of structural and vibrational analyses was carried out. The deformation observed in CM247LC and Nimonic 80A exhibited nearly identical values of 0.965 mm and 0.884 mm, respectively. The results of the vibrational analysis indicated that all materials successfully circumvented the natural frequency as well as the operational natural frequency of 50 Hz, thereby ensuring the safe operation of the gas turbine blade. The findings demonstrated that the CM247LC satisfied both criteria for material selection, making it the most suitable material for gas turbine blade applications when compared to alternative materials. This is due to its comparatively lower deformation despite experiencing a greater magnitude of centrifugal force.